Logistic Efficiency of The Product as A Global Challenge for Modern Industry - Barbara GALINSKA; Maciej BIELECKI (Communications of International Proceedings, 2021)
Product design in the 21st century requires that a number of aspects be taken into consideration. Maximizing the added value for the customer, as described by Porter, is becoming increasingly difficult due to globalization and ever-increasing product personalization. One of the aspects that certainly has an impact on the final cost of a product is the logistics it involves, both on the part of the company and on the part of the consumer. The article presents one of the aspects of design for logistics, i.e. a model of logistic efficiency of the product. Furthermore, an original research method is proposed, based on a case study, including the results of the study carried out at a furniture manufacturing company.
Keywords: Logistically Efficient Product; Design for Logistics; Logistics Management